Development of a robotic driver for autonomous vehicle following. (14th December 2009) - Wong, Nicholas; Chambers, Christopher; Stol, Karl; Halkyard, Roger
This paper presents the development of autonomous control of a passenger vehicle for vehicle following using a robotic driver. The aim is to have a modular and transferable device that can autonomously control a standard passenger car. The robot controls the car in the same way as a human driver, by rotating the steering wheel and pushing the pedals. No permanent modification is required for the host car to be driven by the robotic driver. The robot uses PID controllers for both steering and pedal actuators. Information for motion control is provided by a 6-axis inertial measurement unit with integrated GPS and information about the environment is provided by a laser scanner. The open source Player Project is used as the framework for the controlling software and for simulation of control algorithms. The robotic driver has been tested on a rolling road dynamometer for accelerator and braking response.